Diagnostic yield of cartridge based nucleic acid amplification test in Mycobacterium tuberculosis in a tertiary care medical college and hospital of Southern Odisha, India - Manoranjan, Dash; Samal, Satyajit; Rekha, Swain Trupti; Bibhuprasad, Behera; Swapnasarit, Sahu; Sweekruti, Mahapatra (International Journal of Research in Medical Sciences, 2019)
Background: Tuberculosis is the ninth leading cause of death worldwide. India contributes to about one fifth of global TB burden. It is very important to diagnose early and treat tuberculosis to cut down transmission of tuberculosis. Methods: Author conducted a retrospective study in Department of Pulmonary Medicine SLN Medical College, Koraput, Odisha to analyze the utility and yield of CBNAAT. Study period was from April 2018 to March 2019. Inclusion criteria was all patients whose samples were subjected to CBNAAT were included in our study. Sputum samples from pulmonary tuberculosis patients, and extra pulmonary samples (pleural fluid, ascitic fluid, CSF, synovial fluid and gastric lavage etc. were included in our study population. Exclusion criteria was patients who were under anti tubercular therapy for pulmonary, extra pulmonary and MDR TB were excluded from this study. Data were collected from Pulmonary Medicine Department, ART center, DOTS center and CBNAAT center. Total number of samples tested for CBNAAT, different sample collection sites, age and sex distribution of patients, HIV status of all patients, result of smear microscopy for AFB and CBNAAT and Rifampicin resistance status were analyzed. The detail statistical analysis was done in tabulation form. Results: A total of 2621 samples were tested in CBNAAT during the study period. Mean age of the study population was 38.03 years. 1881 tested were negative and 740 samples were positive for CBNAAT. Of these 2621 samples, 2526 were pulmonary samples (sputum, pleural fluid samples) and 95 were extra pulmonary samples. Author found rifampicin resistance rate of 0.54% (4/740)) in pulmonary tuberculosis cases. There was no rifampicin resistance detected in extra pulmonary samples. CBNAAT could identify 536 cases (23.2%) that were smear negative. Author found TB- HIV co-infection rate of 6.22%. Conclusions: CBNAAT is an important diagnostic modality especially in sputum negative patients for early diagnosis and treatment. In our study it detected Mycobacterium tuberculosis in 23.2% of patients with negative smear for microscopy. Rifampicin resistance rate detected was very low compared to other studies.